Pendidikan Berwawasan Multikultural - Hubertus Muda (STIPAS St. Sirilus Ruteng, 2012)
The concept of multiculturalism is not merely comprehended as an acceptance or acknowledgement of differences. Multiculturalism has come to the fore in philosophical discussionsemphasizing the importance of the acknowledgement of the other as a basis of individual and collective identity formation. And this formationcouldhavebeenpolitical,cultural,religiousinessence.Multiculturalism denotes several cultures exist in a society. It has to do with cultures, and it points out to a plurality of cultures and it refers to a specific manner to responding to that plurality.Dialogue then becomes day to day a Religion in action. It has been a human natural need ofequality and at the same time difference.We are unique not by “exclusion